Sustainable rural electrification using rice husk biomass energy: A case study of Cambodia. (April 2015) - Pode, Ramchandra; Diouf, Boucar; Pode, Gayatri
Abstract: The role of energy in overall social and economical developments is well recognized. However, most energy providers are reluctant to venture in rural regions of developing countries. These regions are generally characterized by: low-income populations, minimum access to electricity, rare access to financial services or loans. In this paper we present the potential of rice husk for rural electrification in Cambodia. Rice husk is locally abundant at almost no cost, with a production over 9.3 million tons paddy rice in 2014 for a total population of about 15 million people. The conversion of rice husk into electricity through gasification or thermally generated electricity is a well-known technology. Rice husk can contribute in a sustainable manner to grant access to electricity to Cambodian rural population and is more reliable and competitive with reference to other renewable energy sources of electricity. The present investigation focuses on the study of self-sustaining energy service model to provide grid quality power to rural populations without the need of subsidies. In Cambodia, many rice mills are operating in rural and semi-urban areas. Some of these mills are now using rice husk for electricity production for industries and rural households, generally for lighting at low cost. We believe that the power systems focusing on both power requirements for the industry such rice mills and power requirements for the people living in the neighboring villages/rural areas at affordable tariff could become the most appropriate solution for the sustainable rural electrification. Along with the potential of rice husk for rural electrification in Cambodia, we present a financially viable business model to provide the grid quality power to rural population without grant or subsidy.